Microalgal production - A close look at the economics - Norsker, N.; Barbosa, M.J.; Vermuë, M.H.; Wijffels, R.H.
Worldwide, microalgal biofuel production is being investigated. It is strongly debated which type of production technology is the most adequate. Microalgal biomass production costs were calculated for 3 different micro algal production systems operating at commercial scale today: open ponds, horizontal tubular photobioreactors and flat panel photobioreactors. For the 3 systems, resulting biomass production costs including dewatering, were 4.95, 4.15 and 5.96 _ per kg, respectively. The important cost factors are irradiation conditions, mixing, photosynthetic efficiency of systems, medium- and carbon dioxide costs. Optimizing production with respect to these factors, a price of _ 0.68 per kg resulted. At this cost level microalgae become a promising feedstock for biodiesel and bulk chemicals.
Keywords: MICROALGAE; PHOTOBIOREACTOR; RACEWAY; TUBULAR; FLAT PANEL; COST; ENERGY; BIOFUEL